2007
DOI: 10.1371/journal.pone.0000447
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for a Link Between Glycolysis and DNA Replication

Abstract: BackgroundA challenging goal in biology is to understand how the principal cellular functions are integrated so that cells achieve viability and optimal fitness in a wide range of nutritional conditions.Methodology/Principal FindingsWe report here a tight link between glycolysis and DNA synthesis. The link, discovered during an analysis of suppressors of thermosensitive replication mutants in bacterium Bacillus subtilis, is very strong as some metabolic alterations fully restore viability to replication mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 92 publications
(96 reference statements)
9
101
0
1
Order By: Relevance
“…Glucose makes important contributions to anabolic processes in all organs of the body providing needed intermediates for cellular proliferation including NADPH, nucleotides for DNA replication (45), and intermediates for fatty acid synthesis (46,47) all largely by way of the pentose phosphate pathway (PPP). In animal experiments, estimates of the amount of glucose entering the PPP in the mature brain have been variable but generally low (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose makes important contributions to anabolic processes in all organs of the body providing needed intermediates for cellular proliferation including NADPH, nucleotides for DNA replication (45), and intermediates for fatty acid synthesis (46,47) all largely by way of the pentose phosphate pathway (PPP). In animal experiments, estimates of the amount of glucose entering the PPP in the mature brain have been variable but generally low (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that these essential enzymes have cellular functions in addition to just providing the cell with the proper metabolic intermediates. Indeed, glycolytic enzymes of E. coli and B. subtilis are involved in mRNA processing and DNA replication, respectively (2,22). It will thus be an important task to identify the essential, secondary functions of the glycerol facilitator and of glycerol kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Although replication fork speed can vary significantly Odsbu et al 2009;Stokke et al 2012), it is not known whether the speed of each individual replication fork is regulated. In Bacillus subtilis, it has been found that replication elongation can be regulated by ppGpp (Wang et al 2007) and metabolic enzymes (Janniere et al 2007). …”
Section: Coordination Of Regulation For Oric and Dnaamentioning
confidence: 99%